Effectiveness of Interactive Learning Media Based on Canva Application on Poster Writing Abilities of Grade VI Students - Dewi, Ramayani; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
This study aims to determine the effectiveness of interactive learning media based on the Canva application on poster-writing abilities of grade VI students of STATE ELEMENTARY SCHOOL 060875 Medan in the 2025-2026 ACADEMIC YEAR. This study used a quantitative method with an experimental approach, specifically a Pre-Experimental Design with a One Group Pretest-Posttest Design. The research sample was all 57 students, selected using Purposive Sampling technique. Data were collected through observation sheets of student and teacher activities, test sheets (pretest and posttest) to measure poster writing skills, and documentation. The results of the descriptive statistical analysis showed that the average pretest score of students' poster writing skills was 43.44, with 100% of students (57 people) not completing the KKM based on the 70. After being given treatment using Canva media, the average posttest score increased significantly to 78.58, with 96.5% of students (55 people) achieving completion. The average increase in scores from pretest to posttest was 35.14%. The results of the normality test showed that the posttest data were not normally distributed, and the homogeneity test showed that the data were not homogeneous. Nevertheless, the hypothesis test using the Paired Samples t-test (noting that a non-parametric test such as the Wilcoxon Signed-Rank Test would be more appropriate given the violation of the assumptions) yielded a significance value (Sig. 2-tailed) of 0.000. Since the significance value of 0.000 < 0.05, the Null Hypothesis (H0) is rejected and the Alternative Hypothesis (H1) is accepted. Based on the results of this study, it is concluded that the use of interactive learning media based on the Canva application is very effective in improving poster writing skills in sixth-grade students at UPT SD Negeri 060875 Medan. Canva media has been proven to improve cognitive learning outcomes and student activity during learning